2015
DOI: 10.1080/10749357.2015.1110306
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy Mediates the Relationship between Balance/Walking Performance, Activity, and Participation after Stroke

Abstract: Background Many outcome measures (OM) that assess individuals’ ability or beliefs in their ability to perform tasks exist to evaluate activity and participation after stroke; however, the relationship between various OM and activity/participation is unclear. Objective The purpose of this study was to explore the relationships between different OM and activity and participation in people after stroke. Methods 59 subjects post-stroke participated in an assessment including self-selected walking speed, 6 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 46 publications
(38 reference statements)
4
43
0
2
Order By: Relevance
“…1, A and B). Walking dysfunction after stroke may result from a variety of deficits, ranging from reduced balance (51,52) to atypical biomechanics. We expected exosuits to have an immediate effect on key biomechanical subtasks that are impaired after stroke, specifically ground clearance by assisting ankle DF during swing phase and propulsive force generation by assisting ankle push-off during stance phase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1, A and B). Walking dysfunction after stroke may result from a variety of deficits, ranging from reduced balance (51,52) to atypical biomechanics. We expected exosuits to have an immediate effect on key biomechanical subtasks that are impaired after stroke, specifically ground clearance by assisting ankle DF during swing phase and propulsive force generation by assisting ankle push-off during stance phase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results agree with those of a previous study that demonstrated that the BBS score was an independent predictor of the RNLI score in a sample of 63 community-dwelling chronic stroke survivors [ 5 ]. It is plausible that good balance performance augments the level of self-efficacy in carrying out daily activities and participating in social life, as demonstrated in a previous study [ 41 ]. A fear of falling [ 42 ] and balance-related self-efficacy [ 5 ] were also found to be independent predictors of community integration in stroke survivors.…”
Section: Discussionmentioning
confidence: 83%
“…Studies showed that there was a correlation between sitting balance and Barthel index score, and sitting balance and gait ability in neurologic disorders 22,[24][25][26][27] . One study showed that trunk control, balance and gait were correlated with daily living activities and functions in patients with chronic stroke 28 . There is evidence in many studies that exercises such as core stability and proprioceptive neuromuscular facilitation improve trunk control, balance, gait and functional independence in patients with stroke [29][30][31] .…”
Section: Discussionmentioning
confidence: 99%